Verbal Communication in the Family - Mamaraimova Zebo Shafoatovna (International Journal on Integrated Education, 2022)
The article provides evidence of the author's hypothesis about the need to separate family communication and communication between relatives as types of everyday communication. Also, information about family communication, professional affiliation of a person, socio-psychological characteristics of family members, personal qualities, family traditions is given.